2015
DOI: 10.1111/codi.12884
|View full text |Cite
|
Sign up to set email alerts
|

COMPRES: a prospective postmarketing evaluation of the compression anastomosis ring CAR 27/ColonRing

Abstract: Nitinol compression anastomosis is safe, effective and easy to use and may offer an advantage for low colorectal anastomosis. A prospective randomized trial comparing ColonRing(™) with conventional stapling is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A retrospective multicentric study including 1’180 patients described an AL rate of 3.22% using the ColonRing device[52]. Further, a prospective postmarketing evaluation of the ColonRing described an AL rate of 5.3% among 266 patients, but a septic anastomotic complication rate of 8.3%, which could reflect the true AL rate[53]. A recent systematic review and meta-analysis including 10 RCT (1’969 patients) found no difference in terms of AL between patients with handsewn or stapled anastomosis (977 patients) and those with compression anastomoses (992 patients)[54].…”
Section: Operative Measures To Prevent Almentioning
confidence: 99%
“…A retrospective multicentric study including 1’180 patients described an AL rate of 3.22% using the ColonRing device[52]. Further, a prospective postmarketing evaluation of the ColonRing described an AL rate of 5.3% among 266 patients, but a septic anastomotic complication rate of 8.3%, which could reflect the true AL rate[53]. A recent systematic review and meta-analysis including 10 RCT (1’969 patients) found no difference in terms of AL between patients with handsewn or stapled anastomosis (977 patients) and those with compression anastomoses (992 patients)[54].…”
Section: Operative Measures To Prevent Almentioning
confidence: 99%
“…Most recently, the nickel‐titanium (nitinol; NiTi) ColonRing device has been introduced with compression rings that possess shape memory and elasticity to provide more uniform compression of the tissue. Despite a large multicentre, multinational study involving 1180 patients , and a prospective multicentre study reporting leakage rates of just over 3% , the device has not gained widespread application.…”
Section: Anastomotic Constructionmentioning
confidence: 99%
“…In the immediate post-operative period, additional medical and surgical procedures prolong hospitalization and increase expense. One recent study revealed a six-fold increase in 30-day mortality following anastomotic leak 49 incidence of leak following compression anastomosis 50,51 . Other novel approaches have been internal bypass and anastomotic sealants 52,53 .…”
Section: Attempts To Reduce Anastomotic Leaks Sd Wexnermentioning
confidence: 99%